Microbial inoculant influences the germination and growth of Albizia lebbeck seedlings in the nursery - Khan, B. M.; Kabir, M. A.; Hossain, M. K.; Mridha, M. A. U. (Banko Janakari, 2016)
Microbial inoculants (MI), a biofertilizer, composed of many different beneficial microorganisms has positive role on seed germination and growth of plants. In the present study, its efficacy on seed germination and seedling growth of Albizia lebbeck in the nursery was studied. The seeds were sown in polybags filled with a mixture of forest soil and cow dung (3:1) and treated with 0.1%, 0.5%, 1%, 2%, 5% and 10% concentrations of MI. Most of the parameters studied (seed germination, shoot and root lengths, dry weights of shoot and root, collar diameter, leaf number etc) were found maximum in 2% of MI . Although the highest vigor index, volume index and quality index (7053, 3738 and 1.106, respectively) were found in 2% MI, but the highest sturdiness (65.95) was found in 1% MI solution. The nodule number was higher at a very low (0.5%) concentration of MI but it normally decreased with the increase of concentration. Total pigment content in leaf was recorded highest (112.86 mg.L-1) in 2% of MI. Therefore, MI influences seed germination and seedling growth of A. lebbeck and the low concentration (2%) of the inoculant can be recommended for getting maximum seed germination and seedling growth of the species studied. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 82-89, 2016